Design of steel structures - Gaylord, Edwin Henry, Jr.; Gaylord, Charles N.; Stallmeyer, James E. (New York : McGraw-Hill, 1992)
This book is about: Loads on structures; Structures, metals, and fasteners; Tension members; Compression members; Beams; Plate girders; Connections; Plastic analysis and design; ...
Includes indexes.
Keywords: Building; Aluminum construction; Building, Iron and steel; Aluminum construction